Atmosphere [electronic resource] : a scientific history of air, weather, and climate - Allaby, Michael (Discovering the Earth, 2009)
Presents an illustrated reference containing information about aspects of the atmosphere, including gases, climate, clouds, exploration of the sky, and weather